Nucleocytoplasmic Distribution of Human RNA-editing Enzyme ADAR1 Is Modulated by Double-stranded RNA-binding Domains, a Leucine-rich Export Signal, and a Putative Dimerization Domain - Strehblow, Alexander (The American Society for Cell Biology, 2002)
The human RNA-editing enzyme adenosine deaminase that acts on RNA (ADAR1) is expressed in two versions. A longer 150-kDa protein is interferon inducible and can be found both in the nucleus and cytoplasm. An amino-terminally truncated 110-kDa version, in contrast, is constitutively expressed and predominantly nuclear. In the absence of transcription, however, the shorter protein is also cytoplasmic and thus displays the hallmarks of a shuttling protein. The nuclear localization signal (NLS) of human hsADAR1 is atypical and overlaps with its third double-stranded RNA-binding domain (dsRBD). Herein, we identify regions in hsADAR1 that interfere with nuclear localization and mediate cytoplasmic accumulation. We show that interferon-inducible hsADAR1 contains a Crm1-dependent nuclear export signal in its amino terminus. Most importantly, we demonstrate that the first dsRBD of hsADAR1 interferes with nuclear localization of a reporter construct containing dsRBD3 as an active NLS. The same effect can be triggered by several other, but not all dsRBDs. Active RNA binding of either the inhibitory dsRBD1 or the NLS bearing dsRBD3 is required for cytoplasmic accumulation. Furthermore, hsADAR1's dsRBD1 has no effect on other NLSs, suggesting RNA-mediated cross talk between dsRBDs, possibly leading to masking of the NLS. A model, incorporating these findings is presented. Finally, we identify a third region located in the C terminus of hsADAR1 that also interferes with nuclear accumulation of this protein.